CLINICAL AND LABORATORY PROFILES OF COMMON PEDIATRIC NEPHRO-UROLOGICAL DISORDERS MANAGED AT THE PEDIATRICS DEPARTMENT, DUC GIANG GENERAL HOSPITAL (2023–2025) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe Clinical and Laboratory Characteristics of Urinary Tract Infections and Nephrotic Syndrome in Children Aged Over 2 Months at Duc Giang General Hospital, 2023–2025Methods: A retrospective and prospective descriptive study was conducted on 50 retrospective medical records collected from January 2023 to December 2024 and 24 prospectively enrolled patients recruited from January 2025 to June 2025.Results: Among common renal and urinary tract diseases treated in the pediatric department, urinary tract infections accounted for 86.4%, while nephrotic syndrome accounted for 13.6%. The mean peripheral white blood cell count was 14.22 ± 4.88 G/L, with leukocytosis observed in 75% of cases. The mean percentage of neutrophils was 52.81 ± 16.6%, with elevated levels found in 12.5% of patients. The mean CRP concentration was 26.2 ± 24.3 mg/L, and elevated CRP was present in 73.4% of cases.Among 64 patients with UTIs, urine culture was performed in 47 cases, yielding 11 positive cultures (17.1%) and 36 negative cultures (56.3%). Escherichia coli was the most isolated pathogen, accounting for 10.9% of cases. Abnormal ultrasonographic findings of renal pelvic dilation were observed in 7.8% of patients.In children with nephrotic syndrome, 70% had a urinary protein-to-creatinine ratio >3000 mg. microscopic hematuria was detected in 40% of cases at level (+) and 10% at level (++). Laboratory findings showed a mean serum albumin level of 19.1 ± 1.6 g/L and a mean total protein level of 44.9 ± 4.6 g/L. Mean serum urea, creatinine, potassium, calcium, and cholesterol levels were 5.0 ± 1.1 mmol/L, 42.9 ± 7.2 µmol/L, 4.0 ± 0.5 mmol/L, 1.8 ± 0.4 mmol/L, and 11.3 ± 1.8 mmol/L, respectively. Ultrasonography revealed ascites in 70% of patients.Conclusion: Children diagnosed with urinary tract infections or nephrotic syndrome at Duc Giang General Hospital exhibited the typical clinical and laboratory manifestations of these conditions. The study’s findings contribute to improving early diagnosis, timely treatment, and the implementation of preventive measures and complication monitoring in affected children at Duc Giang General Hospital.
Keywords: Nephrotic Syndrome, Urinary Tract Infection, Clinical Characteristics and Laboratory Characteristics.